Netwerk / center for contemporary art : Annual 04/05 - Van Bogaert, Pieter; Verhoeven, Thibaut; de Boer, Manon; van den Bossche, Phillip; Netwerk / center for contemporary art, Aalst (Aalst : Netwerk / centrum voor hedendaagse kunst Aalst, 2006)
Asselberghs, Herman ; Bar Amotz, Guy ; Van Bogaert, Pieter ; De Clercq, Anouk ; Crouwers, Alexandra ; Dedobbeleer, Koenraad ; Defrancq, Evert ; Dower, Sean ; Ervinck, Nick ; Floré, Christophe ; Van Gestel, Kristof ; Groner, Sagi ; HAP ; Leib, Anita ; Lerooy, Thomas ; Morrens, Peter ; van Nes, Boris ; Opsomer, Els ; Sakoun, Rebecca ; Vanpevenaege, Yves ; de Ven, Leopold van ; Vernimmen, Anne ; Vester, Ane ; Wharton, Donato ; Witteman, Judith
This book contains a reflection on the exhibitions that took place during the second half of 2004 and 2005
Engels
Nederlands
boek
Keywords: Netwerk